A new species of the genus Zercon (Acari, Zerconidae) from Turkey - Urhan, Ra‘it (Zootaxa, 2007)
A new species of zerconid mite, Zercon kezbaniremae sp. nov., is described from Turkey (Acari: Zerconidae). A key to the adults of the genus Zercon known from Turkey is given.